SURVEI ENTOMOLOGI, MAYA INDEX DAN PERILAKU PEMBERANTASAN SARANG NYAMUK TERHADAP KEPADATAN LARVA AEDES SPP DI DESA KEDIRI, TABANAN - Wiranatha, I Gede Pandu; Purnama, Sang Gede (ARCHIVE OF COMMUNITY HEALTH; Vol 5 No 1 (2018): Juni (2018)DO - 10.24843/ACH.2018.v05.i01.p08, 2020)
ABSTRACT Kediri Village is a Dengue Hemorrhagic Fever endemic area in Tabanan Regency. The behavior of the community in cleaning mosquito breeding sites is not done routinely and the number of containers that can become water reservoirs, especially during the rainy season so that the impact on low rates of larvae free and risk in spreading dengue fever in the environment. This study was conducted to determine the situation of the larvae, virtual index and behavior (knowledge, attitudes, actions) on the density of Aedes spp larvae. Data obtained were analyzed to determine the relationship between independent and dependent variables including knowledge, attitudes, actions, education, employment, virtual index, container index (CI), house index (HI) and breteau index (BI). The results showed that the entomology survey obtained house index (33.11%), container index (10.44%), breteau index (54.54%) and larval free rate (66.89%). Maya index in the high category and bathtub type containers inside the positive house was mostly found (58.8%) while outside the house was positive on used tires (28%). The results of knowledge are classified as good and the level of education is relatively high whereas most respondents work at work. The most significant action on larval density. It is hoped that the community will play an active role in eradicating mosquito nests through 3M plus and health workers will increase regular outreach and larvae monitoring. Keywords : Larvae index ; Behavior ; Characteristic ; Aedes spp.